Suppose you have a product #a*b*c = 0#. Then if any of #a, b# or #c# is equal to zero, the equation is true. This is because any number times zero is equal to zero. For example, if you have #a = 0#, then #0*b*c = 0#, which is true. This is true for any number of terms in the product.

In your case, you have two terms in your product, #(3k)*(k+10) = 0#. As per above, the equation is true when any of the terms are zero. We solve for this algebraically by setting each one to zero.

#3k = 0 -> k = 0#

#k + 10 = 0 -> k = -10#

These are the solutions to the problem.